Molecular discernment and histopathological features of oncogenic Marek’s disease virus among different farmed avian species in Egypt - Maha A.N. Gamal; Eman M.S. El-Nagar; Marwa S. Khattab; Heba M. Salem (Scientific Reports)
Abstract Marek’s disease virus (MDV) is a highly contagious tumor virus that causes detrimental outbreaks in poultry. Since its initial description, the virus’s virulence and acuteness have progressively increased. During this study, we investigated suspected tumorigenic cases of MDV-1 infection among different avian species (chicken, ducks, and turkey) in various Egyptian governorates, including Al-Sharqia, Gharbia, Dakahlia, Port Said, Damietta, and Fayoum, between 2020 and 2023. A molecular study targeting the virulent oncogenic Meq gene revealed that the tumorigenic masses in chicken and duck tissues were identified as virulent MDV-1, but turkeys with cauliflower-like ovarian tumors showed negative results. The isolated MDV-1 strain of chicken origin was given the designation YLE2021 and the sequence was submitted to GenBank with accession number PQ59985. The amino acid sequence of the YLE2021 chicken Meq showed a 296 amino acid length (short Meq), which is characteristic of very virulent Meq and contains seven proline motifs, three of them are interrupted (187 PLQPP 191, 195 PAPP198, 224 PPQPP 228). Experimental infection of one-day-old specific-pathogen-free (SPF) chickens with a strain recovered from a chicken tumor resulted in 40% of infected birds showing the classical neural form of MDV infection. No parenchymal tumors were observed, and the virus could be molecularly detected in the peripheral blood mononuclear cells (PMNCs) of infected and neighboring uninfected SPF birds. In conclusion, this is the first report to identify the presence of MDV-1 in Egyptian ducks. Further investigations are recommended to detect the main cause of the turkeys’ tumor. Continuous molecular monitoring of circulating field viruses is crucial to investigate the mechanisms behind the increase in virus evolution, which could lead to increased virus virulence and allow the virus to evade vaccine protection.